Moral Value Analysis in Serat Kitab Kalam Qodrat for Women’s Moral Education - Anugrah Putri Juniarti; K. Saddhono; Prasetyo Adi Wisnu Wibowo (el Harakah: Jurnal Budaya Islam, 2020)
Morality is a personal guide of distinguishing goodness from badness with their mind. Indonesian women, especially Javanese, are perceived to be moral when they possess noble character reflected in gentle, polite, loyal, and religious attitudes. Many Indonesian cultural products portray the ideal female figure in terms of physical to a moral image. One of the cultural products dedicated to illustrate the typical moral for women is Tambang Macapat. Macapat songs containing moral values for women are the song in Serat Kitab Kalam Qodrat (KKQ). This study focuses on examining the content and moral values of Serat KKQ using gender perspective, with a primary emphasis on women’s gender. The results can be used as a model for Indonesian women and their character education support. This research is qualitative descriptive with a content analysis method. The primary data are the literary works in KKQ from Mpu Tantular Museum collection, Sidoarjo and the thesis of Sri Sulistianingsih (2016) titled Kalam Qodrat book: text edits and structural analysis. The study results are related to women’s morals, respect to parents and a husband (obedient to a husband, loyal, and harmonious), determination, maintaining self-esteem (honor) and the motivation of study. Moralitas merupakan upaya untuk membimbing manusia menggunakan akalnya untuk membedakan kebaikan dan keburukan. Wanita Indonesia khususnya wanita Jawa disebut bermoral ketika memiliki budi pekerti luhur yang tercermin dari sikap lembut, santun, setia dan taat beragama. Banyak produk budaya Indonesia yang menggambarkan sosok perempuan ideal dari segi fisik hingga moralitas. Salah satu produk budaya yang didedikasikan untuk menggambarkan moral ideal bagi perempuan adalah tembang macapat. Salah satu tembang macapat yang memuat nilai moral bagi perempuan adalah tembang macapat yang ada di dalam serat Kitab Kalam Qodrat (KKQ). Fokus studi ini mengkaji isi dan nilai moral dari Serat KKQ menggunakan perspektif gender, dengan fokus utama pada gender perempuan. Hasil kajian dapat digunakan sebagai model bagi perempuan Indonesia serta untuk mendukung pendidikan karakter perempuan. Penelitian ini adalah penelitian deskriptif kualitatif, dengan objek kajian serat KKQ. Menggunakan metode analisis isi. Data utama penelitian ini adalah serat KKQ koleksi museum Mpu Tantular Sidoarjo dan skripsi Sri Sulistianingsih (2016) dengan judul Kitab Kalam Qodrat: suntingan teks dan analisis struktural. Hasil dari penelitian berkaitan dengan moral (akhlak) perempuan, hormat pada orang tua, hormat kepada suami (sikap patuh pada suami, tidak durhaka, setia dan rukun), akhlak berpendirian teguh, menjaga harga diri (kehormatan) serta semangat menuntut ilmu